Hands-On Simulation Modeling with Python: Develop Simulation Models for Improved Efficiency and Precision in the Decision-Making Process - Ciaburro, Giuseppe (Packt Publishing, Limited, 2022)
Hands-On Simulation Modeling with Python, Second Edition teaches you how to leverage Python to develop simulation models and use various Python packages. The book will help you explore various numerical simulation algorithms and concepts, such as the Markov Decision Process, Monte Carlo methods, and bootstrapping techniques.